2016
DOI: 10.1111/ppa.12516
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resistance against the olive‐defoliating Verticillium dahliae pathotype in selected clones of wild olive

Abstract: Verticillium wilt of olive is best managed by resistant cultivars, but those currently available show incomplete resistance to the defoliating (D) Verticillium dahliae pathotype. Moreover, these cultivars do not satisfy consumers' demand for high yields and oil quality. Highly resistant rootstocks would be of paramount importance for production of agronomically adapted and commercially desirable olive cultivars in D V. dahliae‐infested soils. In this work, resistance to D V. dahliae in wild olive clones Ac‐13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 44 publications
9
67
0
Order By: Relevance
“…Disease reactions to the D and ND V. dahliae pathotypes of three AtNPR1 transgenic lines as well as the non-transgenic control P1, which is highly susceptible to this pathogen (Narvaez et al, 2018), were assessed as previously described (Jiménez-Fernández et al, 2016). Monosporic V. dahliae isolates from cotton (V-138: D pathotype, race 2) and olive (V-1242: ND pathotype, race 2; and V-1558: ND pathotype, race 1) (Jiménez-Díaz et al, 2017) were used.…”
Section: Verticillium Dahliae Infection Assaymentioning
confidence: 99%
“…Disease reactions to the D and ND V. dahliae pathotypes of three AtNPR1 transgenic lines as well as the non-transgenic control P1, which is highly susceptible to this pathogen (Narvaez et al, 2018), were assessed as previously described (Jiménez-Fernández et al, 2016). Monosporic V. dahliae isolates from cotton (V-138: D pathotype, race 2) and olive (V-1242: ND pathotype, race 2; and V-1558: ND pathotype, race 1) (Jiménez-Díaz et al, 2017) were used.…”
Section: Verticillium Dahliae Infection Assaymentioning
confidence: 99%
“…Within this holistic framework, the use of tolerant/resistant olive varieties is probably the most efficient and environmentally friendly approach to control VWO. Several studies have focused on the search for sources of genetic resistance to V. dahliae (López‐Escudero et al ., ; Martos‐Moreno et al ., ; Antoniou et al ., ; Colella et al ., ; Trapero et al ., , ; García‐Ruiz et al ., ; Arias‐Calderón et al ., ,b; Jiménez‐Fernández et al ., ), although no cultivar/genotype has been reported as entirely resistant to the pathogen. Some genotypes have been qualified as tolerant (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed V. dahliae YFP transformant proved suitable for the study because it did not show any difference compared with the wild type strain V. dahliae V‐138I regarding morphology and growth rate on different culture media. The transformant strain retained the parental virulence phenotype, as shown by the severe defoliation and plant death (mean symptoms severity = 4 on a 0–4 rating scale) induced on susceptible Picual olive 7 weeks after inoculation, a disease reaction similar to that found for the parental isolate on Picual olive in previous work (Jiménez‐Díaz et al ., ; Jiménez‐Fernández et al ., ). Also, no significant differences ( P ≥ 0.05) were found in the antagonistic ability of T. harzianum GFP22 against V. dahliae V‐138I and V. dahliae V138I‐YFP.…”
Section: Discussionmentioning
confidence: 97%
“…However, most commercial olive cultivars lack suitable resistance to the highly virulent D pathotype of V. dahliae that has become widespread in Spain and also occurs elsewhere (Jiménez‐Díaz et al ., ; Trapero et al ., ). In previous studies, three wild olive clones were identified that proved resistant to D V. dahliae , and these are used as rootstock for grafting D V. dahliae ‐susceptible olive cultivars in commercial production (Jiménez‐Fernández et al ., ; Palomares‐Rius et al ., ). Here, the potential of combining T. harzianum with use of a resistant wild olive rootstock was investigated for enhancing the integrated management of D V. dahliae ‐induced VW in olive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation